Constrained-Spherical Deconvolution Tractography in the Evaluation of the Corticospinal Tract in Glioma Surgery - Sheng, Zhiyuan; Yu, Jinliang; Chen, Zhongcan; Sun, Yong; Bu, Xingyao; Wang, Meiyun; Sarica, Can; Hernesniemi, Juha; Nelson, Bradley J.; Zemmar, Ajmal; Avecillas-Chasin, Josue M. (Frontiers in Surgery, 2021)
Introduction: Tractography has demonstrated utility for surgical resection in the setting of primary brain tumors involving eloquent white matter (WM) pathways. Methods Twelve patients with glioma in or near eloquent motor areas were analyzed. The motor status was recorded before and after surgery. Two different tractography approaches were used to generate the motor corticospinal tract (CST): Constrained spherical deconvolution probabilistic tractography (CSD-Prob) and single tensor deterministic tractography (Tens-DET). To define the degree of disruption of the CST after surgical resection of the tumor, we calculated the percentage of the CST affected by surgical resection, which was then correlated with the postoperative motor status. Moreover, the fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD) of the CST generated by the CSD-Prob and the Tens-DET was measured and compared between the ipsilesional and contralesional side. Results The CST was identified in all patients and its trajectory was displaced by the tumor. Only the CSD-Prob approach showed the CST with the characteristic fan-like projections from the precentral gyrus to the brainstem. Disruption of the CST was identified in 6/6 with postoperative motor deficit by CSD-Prob approach and in 5/6 in the Tens-DET. The degree of disruption was significantly associated with the motor deficit with the CSD-Prob approach (rho=-0.88 p=0.021). However, with the Tens-DET approach the CST disruption did not show significant association with the motor function (rho=-0.27 p=0.6). There was a significant decrease in FA (p=0.006) and a significant increase in MD (p=.0004) and RD (p=0.005) on the ipsilesional CST compared with the contralesional CST only with the CSD-Prob approach. Conclusion CSD-Prob accurately represented the known anatomy of the CST and provided a meaningful estimate of microstructural changes of the CST affected by the tumor and its macrostructural damage after surgery. Newer surgical planning stations should include advanced models and algorithms of tractography in order to obtain more meaningful reconstructions of the WM pathways during glioma surgery.